Ignorance as Lack of Imagination (of the other) in Jean-Jacques Rousseau’s Philosophy - ERŐSS, Réka (Studia Universitatis Babeș-Bolyai Philosophia, 2025)
In Rousseau’s thinking the anthropological difference is marked by the faculty of imagination, thus challenging the enlightenment consensus on the supremacy of ration. This paper discusses the significance of imagination within Rousseauean philosophical anthropology and philosophy of language, relying mainly on Jean Starobinski’s and Jacques Derrida’s interpretations. I argue that imagination, which preeminently requires the presence of the other, is the vital spark in the savage man’s becoming a social being.